Numerical modelling of free thin film dynamics - Popova, L.; Gromyko, G.; Tabakova, S. (Mathematical Modelling and Analysis, 2003)
The dynamics of a free thin film attached to a rectangular frame surrounded by an ambient gas is studied theoretically. The mathematical model is described by evolutionary nonlinear system for the longitudinal velocity components and film thickness. The 1D form of the nonstationary problem is solved by a finite difference scheme. The film shape evolution in time is tracked at different Reynolds numbers, Re. The steady state solutions are reached asymptotically in time for a large range of Re.Laisvosios plonosios plėvelės dinamikos skaitinis modeliavimasSantrauka. Nagrinėjamas svarbus dujų dinamikai plonosios plėvelės judėjimo matematinio modeliavimo uždavinys. Atlikta diferencialinių lygčių asimptotinė analizė. Pasiūlyta skirtuminė schema skaičiavimams atlikti ir pateikti skaitinių eksperimentų rezultatai.First Published Online: 14 Oct 2010